The Effectiveness of the Liveworksheet Assisted Project Based Learning Model on Mathematical Literacy in View of Student Learning Motivation - Triningsih, Novi; Amidi, Amidi (Unnes Journal of Mathematics Education, 2023)
The mathematical literacy of students at SMP Negeri 26 Semarang is not yet optimal. This research aims to determine learning mastery, average student mathematical literacy, the influence of learning motivation on mathematical literacy, and describe students' mathematical literacy in terms of learning motivation in class using a project based learning model assisted by live worksheets. This research used a mixed-method explanatory sequential design. The quantitative method in this research used a true experimental design with a posttest-only control group design involving two groups as an experimental group and a control group.The population of this study was class VIII of SMP Negeri 26 Semarang. The sample for this research was class VIII-G as the experimental class and class VIII-E as the control class taken using simple random sampling techniques. The subjects of this research consisted of 2 students in each category of high, medium and low learning motivation who were selected using purposive sampling technique. The results of this research show that: (1) students' mathematical literacy in Project Based Learning with Liveworksheet assistance has reached the actual completion limit; (2) the average mathematical literacy of students in Project Based Learning assisted by Liveworksheets is better than the average mathematical literacy of students in Problem Based Learning; (3) There is an influence of learning motivation on students' mathematical literacy with a percentage of 42.8%; (4) Subjects with high learning motivation have high mathematical literacy abilities because they tend to be able to fulfill the three indicators well. Subjects with moderate learning motivation have moderate mathematical literacy abilities, because there are still indicators that have not been met properly. Subjects with low learning motivation have low mathematical literacy abilities, because they do not fulfill the three indicators well.